CLINICAL AND MORPHOLOGICAL INTERRELATIONS OF EXTRAHEPATIC BILE DUCTS IN COMPLICATED CHOLELITHIASIS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The clinical material consisted of 127 patients with complicated forms of cholelithiasis, accompanied by lesions of the extrahepatic bile duct of varying severity, who were treated and examined at the Republican Scientific Center for Emergency Medical Care of the Ministry of Health of the Republic of Uzbekistan and at the Department of Faculty and Hospital Surgery of the Bukhara State Medical Institute named after Abu Ali Ibn Sina in the period from 2020 to 2025. All patients were divided into two chronological groups according to the conditions of the study: the control group, including 62 (48.8%) patients treated in 2020-2022 using traditional laparoscopic surgery methods, and the main group, consisting of 65 (51.2%) patients operated on in 2023-2025 using developed technologies for diagnosis, prognosis, and surgical treatment of lesions of the extrahepatic bile duct.